Once upon a time: children’s stories of Eco-School Learning - Ritch, Elaine; Dodd, Christopher A (2018)
The retail environment within the UK is highly competitive and retailers seek to position value that will appeal to consumers. There are a number of strategies that retailers will adopt to align with consumer value, and since the global economic crisis of 2008 and the UK governments subsequent implementation of austerity policy, many retailers have focused on being price led. This is evident with the expansion of international discount retailers entering into the UK marketplace (for example Lidl, Aldi, Primark, H&M) and the increase of UK discount retailers (for example Poundland, B&M, The Range); as a result, many established UK retailers have struggled to compete (Brian, 2017), leading to the store closures of established UK retailers (House of Fraser, Marks and Spencer’s, Debenhams) and job losses. As such, retailers may seek alternative positions of value and this research seeks to explore if addressing growing concerns for sustainable development could provide a competitive advantage. Sustainability is a point of value that is regaining traction, stimulated by concerns for climate change and the detrimental impact that production, consumption and disposal has upon the environment (Agdar et al., 2005). Inspired by visual imagery, such as the BBC’s Blue Planet series that featured the impact of single use plastic in the oceans (Turner, 2017) and Non-Government Organisations (NGO), such as Greenpeace, sharing photographs of the impact of waste upon wildlife, attention has turned towards how retailers can innovate within the supply chain to support consumers’ adoption of sustainability. One example from UK supermarket Iceland offers a point of differentiation that addresses sustainability with their recent partnership with Greenpeace to produce a Christmas advert that illustrates the impact of palm oil on deforestation and the orangutan population. Despite being banned by the UK body that pre-approves television advertising the advert has been widely shared on social media, illustrating consumer ...